Energy Storage: Novel Polygonal Vanadium Oxide Nanoscrolls as Stable Cathode for Lithium Storage (Adv. Funct. Mater. 12/2015). (March 2015) - Wei, Qiulong; Tan, Shuangshuang; Liu, Xiaoyi; Yan, Mengyu; Wang, Fengchao; Li, Qidong; An, Qinyou; Sun, Ruimin; Zhao, Kangning; Wu, Hengan; Mai, Liqiang
Abstract : Constructing a self‐buffered nanostructure is demonstrated to be a facile and effective strategy to enhance lithium battery performance. On page 1773 L. Mai and team construct a novel polygonal nanoscroll (PNS) structure via the self‐rolling, Ostwald ripening and scroll‐by‐scroll mechanism. This novel PNS structure offers the robust outer wall and expandable inner space to buffer the swelling stress during Li+ ion intercalation/extraction, which effectively improves the cycling stability.